Płeć metrykalna i psychologiczna a podział obowiązków domowych i satysfakcja seksualna w związkach konsensualnych = Metrical and psychological sex versus the division of household duties and sexual satisfaction in consensual relationships - Bakiera, Lucyna; Wiśniewska, Magdalena (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of this study was to verify whether, in the case of consensual (cohabitating) couples, metrical and psychological sexes are linked to the division of household duties and to sexual satisfaction. The study involved 46 young adults aged 21-35 (25 women and 21 men). Their psychological sex was examined using Inwentarz Płci Psychologicznej (Psychological Sex Inventory) by Kuczyńska (1992). Also, Sexual Satisfaction Scale by Deborah Davis (2006) was applied. The division of household duties was assessed using a tool constructed for the purposes of the study. The research allows concluding that neither metrical nor psychological sex can be clearly linked to taking care of the household or to sextual satisfaction. Independently of the psychological sex, housekeeping is the domain of women more frequently than of men.
Keywords: płeć metrykalna; płeć psychologiczna; obowiązki domowe; satysfakcja seksualna; kohabitacja; metrical sex; psychological sex; household duties; sexual satisfaction; consensual relationship